2005
DOI: 10.1158/1078-0432.ccr-05-0427
|View full text |Cite
|
Sign up to set email alerts
|

Radiation and Transforming Growth Factor-β Cooperate in Transcriptional Activation of the Profibrotic Plasminogen Activator Inhibitor-1 Gene

Abstract: Radiation-induced fibrosis is an important side effect in the treatment of cancer. Profibrotic proteins, such as plasminogen activator inhibitor-1 (PAI-1), transforming growth factor-h (TGF-h), and tissue type inhibitor of metalloproteinases-1 (Timp-1), are thought to play major roles in the development of fibrosis via the modulation of extracellular matrix integrity.We did a detailed analysis of transcriptional activation of these profibrotic genes by radiation and TGF-h. Irradiation of HepG2 cells led to a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 51 publications
4
53
0
Order By: Relevance
“…PAI-1 expression is induced rapidly in the endothelium in irradiated skin. Moreover, ionizing radiation was shown to increase PAI-1 expression in NRK52E [30] and HEPG2 cells [31]. Additionally, PAI-1 over-expression is observed in radiation-induced nephrosclerosis [32] and in human radiation enteritis and intestinal lesion [33,34] underlining a role for PAI-1 in radiation-induced tissue damages.…”
Section: Discussionmentioning
confidence: 99%
“…PAI-1 expression is induced rapidly in the endothelium in irradiated skin. Moreover, ionizing radiation was shown to increase PAI-1 expression in NRK52E [30] and HEPG2 cells [31]. Additionally, PAI-1 over-expression is observed in radiation-induced nephrosclerosis [32] and in human radiation enteritis and intestinal lesion [33,34] underlining a role for PAI-1 in radiation-induced tissue damages.…”
Section: Discussionmentioning
confidence: 99%
“…16 Moreover, PAI-1 overexpression has been described in radiation-induced nephrosclerosis 17 and in human radiation enteritis, 18 suggesting a role of PAI-1 in radiation-induced normal tissue damage. We have clearly demonstrated that PAI-1 plays a crucial role in radiation-induced intestinal lesions following a high single dose of radiation.…”
Section: Discussionmentioning
confidence: 99%
“…PAI-1 was described as a direct target of p53 32 in tumor cells and the mutation of the p53 binding element in the PAI-1 promoter abolished the radiation-induced PAI-1 transcription in HEPG2 cells. 16 Radiation and TGF-␤ cooperate in the radiation-induced PAI-1 transcription, suggesting that a p53/Smad pathway is involved in this mechanism. Moreover, a specific cooperation and physical interaction of Smads with p53 play a key role in embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the coding sequence of the different chaperones was amplified using the primers listed in supplemental Table 8. As a template source, complementary DNA (cDNA) was made from total RNA as previously described (Hageman et al 2005). As a source of total RNA, QPCR Human reference Total RNA (Stratagene) was used, which is a mixed source of RNA from the following cell line derivations: adenocarcinoma, mammary gland; hepatoblastoma, liver; adenocarcinoma, cervix; embryonal carcinoma, testis; glioblastoma, brain; melanoma, skin; liposarcoma, histiocytic lymphoma, macrophage, histocyte; lymphoblastic leukemia, T lymphoblast; plasmacytoma, myeloma, B lymphocyte.…”
Section: Gene Cloningmentioning
confidence: 99%